Genetic stability of white Kelampayan (neolamarckia cadamba) plantlets derived from callus as explant using ISSR markers - Ngo, Yi Lei (Universiti Malaysia Sarawak (UNIMAS), 2016)
Neolamarckia cadamba or generally known as white Kelampayan has been perceived as one of the potential fast growing tree species suitable for forest plantation establishment in Sarawak, Malaysia due to its multipurpose and high commercial values. Hence, micropropagation is a prevalent method to obtain sufficient amount of unifrom plants. In the present study, in vitro propagation of Kelampayan was attempted through multiple shoot regeneration from both callus and nodal segments cultured on Gamborg's B5 medium supplemented with various combinations of BAP, NAA and CWo 1.0 mg/L BAP was found to be the most effective for shoot regeneration from callus explants (9.09%) and produced multiple shoots (1.6) per explant. Repeated subculturing of newly fonned nodal parts after each harvest up to third passage, yielded higher number of shoots (1.97) per explant was obtained. Inter Simple Sequence Repeats (ISSR) marker was used to detennine the genetic stability of micropropagated and stock plants of Kelampayan. ISSR primers, (GTG)6 had generated an average of 6.5 clear bands, of which 36.11 % of the loci were polymorphic among 77 Kelampayan samples. All ISSR profiles from micropropagated plants were closely monomorphic and similar to the mother plants, while low variation was induced in the second subculture cycle. The genetic diversity, estimated by Shannon's index, was 0.1862, revealing a low level of genetic variation among them. The results indicated that genetic instability was obtained among the micropropagated Kelampayan plantlets when subcultured to second cycle.